The Influence of Internal Control and Integrity Employee to The Fraud Prevention - Rizqita Nurul Ridwani Putri; Mentari Putri Pertiwi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The development of the world in doing business in the era of Industry 4.0 which is increasingly fast and varied has resulted in increasing competition between companies and the problems faced by companies are increasingly complex. The more complex the problems faced often deviate far from moral activities and no longer consider integrity. This study aims to determine the effect of internal control and employee integrity on fraud prevention. The object of this research is the Public Works and Spatial Planning Service Bandung Regency. The data used in this study is primary data and uses a data collection method using a questionnaire. This Study uses descriptive analysis and verification methods statistically processed SPSS 26. The results show that 1) internal control effect on fraud prevention 2) employee integrity effect on fraud prevention 3) internal control and employee integrity effect on fraud prevention.